1982
DOI: 10.1017/s0022215100092203
|View full text |Cite
|
Sign up to set email alerts
|

What's best in myringoplasty: underlay or overlay, dura or fascia?

Abstract: Results of 1065 operations (604 myringoplasties‡ and 461 tympanoplasties §) performed by a single surgeon using either underlay homograft dura, underlay autograft temporalis fascia or overlay autograft temporalis fascia are compared.Pre-operative and operative conditions are analysed to determine which of these influence results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 9 publications
3
36
0
1
Order By: Relevance
“…Myringoplasty using TFG and underlay technique had hearing improvement in 70-80 % of patients at the end of 1 year follow up [9,17]. In a study by Packer et al [17] reported average AB gap closure was 11.8 dB. In our study average AB gap closure was 16.09 dB.…”
Section: Hearing Improvementsupporting
confidence: 48%
See 3 more Smart Citations
“…Myringoplasty using TFG and underlay technique had hearing improvement in 70-80 % of patients at the end of 1 year follow up [9,17]. In a study by Packer et al [17] reported average AB gap closure was 11.8 dB. In our study average AB gap closure was 16.09 dB.…”
Section: Hearing Improvementsupporting
confidence: 48%
“…In a study by Adkins and White [14] 25 % adult myringoplasty failures and 75 % of failures in children were observed in cases with bilaterally discharging ears. But according to the study by Packer et al [17] where overall result of myringoplasty success was close to 90 %, the success rate with bilateral chronic otitis media cases was 87 %; the difference was not statically significant.…”
Section: Graft Successmentioning
confidence: 92%
See 2 more Smart Citations
“…(Fig. 1) In overlay technique there are chances of anterior canal wall blunting, lateralisation of the graft, formation of epithelial pearls, excessive membrane thickness, and longer duration of healing and increased risk of iatrogenic cholesteatoma [4][5][6]. The disadvantages of underlay technique are that the middle ear space is reduced, there are chances of medialisation of the graft [6], less suitable for large anterior perforations [7] and longer healing time.…”
Section: Introductionmentioning
confidence: 99%